Degradation of ZIF-8 in phosphate buffered saline media - Velsquez-Hernndez, Miriam de J; Ricco, Raffaele; Carraro, Francesco; Limpoco, F. Ted; Linares-Moreau, Mercedes; Leitner, Erich; Wiltsche, Helmar; Rattenberger, Johannes; Schrttner, Hartmuth; Frhwirt, Philipp; Stadler, Eduard M; Gescheidt, Georg; et al. (CrystEngComm, 2019)
Understanding the stability of zeolitic imidazolate framework-8 (ZIF-8) under physiological conditions is critical in biotechnology and biomedicine for biosensing, biocatalysis, and drug delivery. The use of ZIF-8 has shown that this metal organic framework (MOF) and its derived bio-composites can degrade in presence of buffer solutions. Here we present an in-depth analysis of the structural and chemical changes of pure ZIF-8 particles exposed to phosphate buffered saline (PBS) media. Two different particle sizes (2 m and 250 nm) were selected and the decomposition operated by 10 mM PBS (aka 1X) was studied using powder X-ray diffraction (PXRD), Fourier transformed infrared spectroscopy (FTIR), time resolved atomic force microscopy (AFM), in situ small angle X-ray scattering (SAXS), and 31 P NMR. Understanding the stability of zeolitic imidazolate framework-8 (ZIF-8) under physiological conditions is critical in biotechnology and biomedicine for biosensing, biocatalysis, and drug delivery.